2018
DOI: 10.1155/2018/1694567
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical Characteristics and Genesis Model of Jinjiang and Julong Hot Springs in Changbai Mountain, Northeast China

Abstract: Changbai Mountain in China has been explored as a potential area for its rich hot springs including the Jinjiang and Julong hot spring groups. The hydrogeochemical characteristics and conceptual genesis models of the Jinjiang and Julong hot springs were evaluated by hydrogeochemical analysis, isotope analysis, rock sample analysis, hydrogeochemistry simulation, and geophysical exploration method. The results showed that HCO3− and Na+ were the most abundant anion and cation in the hot springs, and the hydrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Baekdu area. Recently, Yan et al [8][9][10] reported that chemical compositions of the hot spring and mineral (spring) water in Mt. Baekdu were produced from water-rock interaction through the deep and long water cycle of the thermal water.…”
Section: Introductionmentioning
confidence: 99%
“…Baekdu area. Recently, Yan et al [8][9][10] reported that chemical compositions of the hot spring and mineral (spring) water in Mt. Baekdu were produced from water-rock interaction through the deep and long water cycle of the thermal water.…”
Section: Introductionmentioning
confidence: 99%
“…Julong geothermal spring water is enriched with minerals such as Na, Ca, Mg, Fe, Cu, and Mn [30]. Trace components such as H 2 SiO 3 , Li, and Sr are also abundant [30,31]. The geothermal fluid in the Julong hot springs is characterized by temperatures between 70 and 83 • C [32] and pH from weakly alkaline to alkaline (7.44-8.17) [33].…”
Section: Introductionmentioning
confidence: 99%
“…The geothermal fluid in the Julong hot springs is characterized by temperatures between 70 and 83 • C [32] and pH from weakly alkaline to alkaline (7.44-8.17) [33]. Gases related to mantle magmatic activity, which are released from the hot spring area, include CO 2 , N 2 , H 2 , He, and CH 4 , with CO 2 being the most abundant [31,34]. Sinter caked in the hot spring region is expected to host unusual thermophilic biota that may provide clues to ancient life on Earth and possibly Mars [35].…”
Section: Introductionmentioning
confidence: 99%
“…Changbai Mountain (42°8'25.4004”N, 128°7'36.2352″E) extends along the border between the Chinese provinces Jilin and Liaoning and North Korea, with the “Changbaishan” being the highest mountain (2750 m asl). Samples were taken along the northern slope of the mountain forming part of the “Changbaishan National Nature Reserve.” The alkaline geological groups in the sampling area comprise stomatal and laminated basalt, alkali pumice, trachyte and tuff, reflecting the volcanic history of the mountain (Yan et al, 2018). The area belongs to the temperate climate regime and is characterized by long winters and short and warm summers.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were taken along the northern slope of the mountain forming part of the "Changbaishan National Nature Reserve." The alkaline geological groups in the sampling area comprise stomatal and laminated basalt, alkali pumice, trachyte and tuff, reflecting the volcanic history of the mountain (Yan et al, 2018). The area belongs to the temperate climate regime and is characterized by long winters and short and warm summers.…”
Section: Study Site and Samplingmentioning
confidence: 99%